Case report: Oral anticoagulant combined with percutaneous coronary intervention for peripheral embolization of left ventricular thrombus caused by myocardial infarction in a patient with diabetes mellitus - Zhu, Chao; Zhou, Li; Gao, Hongli; Wang, Jiali; Li, Jiayu; Chen, Hui; Li, Hongwei (Frontiers in Cardiovascular Medicine, 2022)
Background Left ventricular thrombus (LVT) is a well-recognized complication of myocardial infarction (MI) in patients with diabetes. An embolic complication caused by LVT is a key clinical problem and is associated with worsened long-term survival. Case presentation A 45-year-old man with persistent left abdominal pain for 1 week and left leg fatigue was admitted to the emergency department. The cause of abdominal pain was embolism of the renal artery, the splenic artery, and the superior mesenteric artery caused by cardiogenic thrombosis, which further led to splenic infarction and renal infarction. It was unclear when MI occurred because the patient had no typical critical chest pain, which may have been related to diabetic complications, such as diabetic peripheral neuropathy. Diabetes plays a pivotal role in MI and LVT formation. Because coronary angiography suggested triple vessel disease, percutaneous transluminal coronary angioplasty (PTCA) was conducted, and two drug-eluting stents were placed in the left anterior descending coronary artery (LAD). Due to a lack of randomized clinical control trials, the therapy of LVT and associated embolization has been actively debated. According to the present guidelines, this patient was treated with low-molecular-weight heparin and warfarin (oral anticoagulants) for 3 months in addition to aspirin (100 mg/day) and clopidogrel (75 mg/day) for 1 year. No serious bleeding complications were noted, and a follow-up examination showed no thrombus in the left ventricle or further peripheral thrombotic events. Conclusion Peripheral embolization of LVT caused by MI leading to multiple organ embolization remains a rare occurrence. Diabetes plays a pivotal role in MI and LVT formation. Successful revascularization of the infarct-related coronary artery and anticoagulation therapy is important to minimize myocardial damage and prevent LVT. The present case will help clinicians recognize and manage LVT in patients with diabetes and related peripheral arterial thrombotic events with anticoagulation.